Informação & Informação Vol. 15, No. 2 (2010) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2012)
Link de acesso ao número: http://www.uel.br/revistas/uel/index.php/informacao/issue/view/618